2015
DOI: 10.1088/1748-9326/10/5/054015
|View full text |Cite
|
Sign up to set email alerts
|

Arctic moisture source for Eurasian snow cover variations in autumn

Abstract: Eurasian fall snow cover changes have been suggested as a driver for changes in the Arctic Oscillation and might provide a link between sea-ice decline in the Arctic during summer and atmospheric circulation in the following winter. However, the mechanism connecting snow cover in Eurasia to seaice decline in autumn is still under debate. Our analysis is based on snow observations from 820 Russian land stations, moisture transport using a Lagrangian approach derived from meteorological re-analyses. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 43 publications
8
68
0
Order By: Relevance
“…However, for these months some moisture contribution appears affecting continental areas, especially over northern Eurasia. This result is in agreement with previous publications that suggest an influence from the Arctic over Eurasia (Liu et al, 2012;Wegmann et al, 2015). Wegmann et al (2015) have suggested a relation between the increased moisture evaporation over Barents and Kara Sea and higher snow precipitation over Siberia in autumn.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, for these months some moisture contribution appears affecting continental areas, especially over northern Eurasia. This result is in agreement with previous publications that suggest an influence from the Arctic over Eurasia (Liu et al, 2012;Wegmann et al, 2015). Wegmann et al (2015) have suggested a relation between the increased moisture evaporation over Barents and Kara Sea and higher snow precipitation over Siberia in autumn.…”
Section: Discussionsupporting
confidence: 94%
“…This result is in agreement with previous publications that suggest an influence from the Arctic over Eurasia (Liu et al, 2012;Wegmann et al, 2015). Wegmann et al (2015) have suggested a relation between the increased moisture evaporation over Barents and Kara Sea and higher snow precipitation over Siberia in autumn. Despite form our results such relation cannot be addressed, some moisture contribution can be found from these seas (Figs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The size of the target regions in this study (Arctic region and subregions) is bigger than in many of the regions where the same methodology was used in previous studies (e.g. Ramos et al, 2016or Wegmann et al, 2015 and the average number of particles by source that reach the target regions high enough daily (see Table S1 in the Supplement).…”
Section: Estimation Of the Lagrangian Moisture Transport From The Maimentioning
confidence: 96%
“…Moreover, the duration of the winter sea ice cover in the White Sea, south of the Kola Peninsula, has declined by about 10 days per decade since 1979 (Parkinson 2014). Anomalously low sea ice extent in the Barents Sea, particularly during winter, leads to higher turbulent heat fluxes that warm the region diabatically (e.g., Serreze et al 2011) and has led to changes in regional circulation patterns ) and snow cover (Wegmann et al 2015). Composite analysis by Inoue et al (2012) revealed that reduced ice in the Barents Sea is associated with a blocking high (anticyclone) over the Siberian coast, which results in a northward expansion and deepening of the climatological Siberian high (SH) pressure.…”
Section: Introductionmentioning
confidence: 99%